Review of Energy Harvesting for Buildings Based on Solar Energy and Thermal Materials - Luciana Sucupira; João Castro-Gomes (CivilEng, 2021)
Reducing the use of fossil fuels and the generation of renewable energy have become extremely important in today. A climatic emergency is being experienced and society is suffering due to a high incidence of pollutants. For these reasons, energy harvesting emerges as an essential source of renewable energy, and it benefits from the advancement in the scope of solar and thermal energy which are widely abundant and usually wasted. It is an option to obtain energy without damaging the environment. Recently, energy harvesting devices, which produce electricity, have been attracting more and more attention due to the availability of new sources of energy, such as solar, thermal, wind and mechanical. This article looks at recent developments in capturing energy from the sun. This literature review was performed on research platforms and analyzes studies on solar and thermal energy capture carried out in the last four years. The methods of capturing solar energy were divided according to how they were applied in civil engineering works. The types of experiments carried out were the most diverse, and several options for capturing solar energy were obtained. The advantages and disadvantages of each method were demonstrated, as well as the need for further studies. The results showed that the materials added to the components obtained have a lot of advantages and could be used in different energy capture types, such as photovoltaic, thermoelectric generators, pyroelectricity and thermometrical. This demonstrates that the capture of solar energy is quite viable, and greater importance should be given to it, as the number of research is still small when compared to other renewable energies.